The Importance of Educational Attainment and Premarital Counseling in Building Family Harmony and Preventing Domestic Violence to Strengthen National Resilience - Gita Prismadianto; Endrawati, Lucky; Putra, Fadillah (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study aims to analyze the role of premarital education and guidance outcomes in building family harmony and supporting national resilience. The family as the smallest social unit has a strategic role in creating a strong and stable society, which in turn supports national resilience. To achieve this goal, the research used a Systematic Literature Review (SLR) approach that utilized PRISMA guidelines in identifying, screening and synthesizing relevant literature. Through in-depth analysis, the study found that premarital education and guidance play a crucial role in shaping individuals' mindsets and skills, which are essential in leading a harmonious married life. Moreover, these programs are designed to equip prospective couples with the knowledge and skills necessary to create a balanced and healthy relationship, ultimately contributing to national resilience. The government has an important role in developing effective strategies through premarital education and guidance programs, including increased accessibility, integration of family policies, and program monitoring and evaluation. This comprehensive approach is expected to create stable and productive families, which are the foundation for national resilience. This study suggests strengthening policies and programs on premarital education and guidance, increasing accessibility, especially in remote areas, effective monitoring and evaluation, and improving the quality of human resources through training premarital counselors. In conclusion, premarital education and guidance play an important role in maintaining family harmony and strengthening national resilience.